2012
DOI: 10.3109/14767058.2012.714995
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposing factors to bronchopulmonary dysplasia: preliminary data from a multicentre study

Abstract: Bronchopulmonary dysplasia (BPD) is the most frequent chronic lung disease in preterm newborn infants. It is a multifactorial disease caused by the interaction between environmental and genetic factors. The aim of this study is to identify genetic variants contributing to BPD development using next-generation sequencing (NGS) technology. We prospectively evaluated 378 premature newborn infants with a gestational age <32 weeks in a multicentre study from 12 Italian neonatal intensive care unit from 2009 to 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
0
8
0
3
Order By: Relevance
“…We need to continue to seek insights into the basic mechanisms of neonatal lung development, injury and repair in order to identify novel targets for intervention. In addition, ongoing research focused on genetic determinants of BPD may lead to targeted therapeutic approaches based on host factors and specific patient genetic and epigenetic makeup 99 . Finally, development of prediction tools for BPD based on perinatal and postnatal risk factors may prove very useful in stratifying patients by risk category in future RCTs of new interventions 100 .…”
Section: Resultsmentioning
confidence: 99%
“…We need to continue to seek insights into the basic mechanisms of neonatal lung development, injury and repair in order to identify novel targets for intervention. In addition, ongoing research focused on genetic determinants of BPD may lead to targeted therapeutic approaches based on host factors and specific patient genetic and epigenetic makeup 99 . Finally, development of prediction tools for BPD based on perinatal and postnatal risk factors may prove very useful in stratifying patients by risk category in future RCTs of new interventions 100 .…”
Section: Resultsmentioning
confidence: 99%
“…These models could then be refined for example by adding genetic susceptibility as a predictor [63]. However, more research is needed to determine which of the suggested multiple candidate genes will increase accuracy of a prediction model [64]. Another improvement in the clinical prediction models could come from using birth weight Z scores in addition to gestational age instead of combining gestational age and birth weight in the model.…”
Section: Discussionmentioning
confidence: 99%
“…Many potential risk factors have been identified for the development of BPD (see Fig. 1) including lower gestational age, 9 low birth weight for gestational age, 10 white race, 11 male gender, 12 genetic factors 13 and other common sequelae during the neonatal period such as intraventricular haemorrhage, necrotizing enterocolitis, patent ductus arteriosis or sepsis. [14][15][16] The current consensus definition determines BPD at 36 weeks post-menstrual age (PMA) in infants born less than 32 weeks gestation who required supplementary oxygen for at least respiratory support at 36 weeks PMA.…”
Section: Definition and Risk Factors For Bpdmentioning
confidence: 99%